Assessing mineral composition and permeability of a shale seal. Issue 1 (1st December 2019) - Beloborodov, Roman; Pervukhina, Marina; Lebedev, Maxim; Hauser, Juerg
Summary: Predicting the mineralogical composition of shales is crucial for drilling operations related to hydrocarbon exploration/production as well as for the assessment of their sealing capacity as hydrocarbon or CO2 barriers. Despite the importance of inferring the mineralogical composition, few methods have been developed. A regional smectite-rich seal with a thickness of more than 1 km is hindering hydrocarbon exploration in the Northern Carnarvon Basin, North West Shelf of Australia. The complex structures of the channelised oil and gas fields in the area make it necessary to drill deviated wells through that seal. The maximum deviation angle at which successful drilling is possible strongly depends on the fraction of swelling clay minerals in shale composition, in particular, on the smectite content. Here we introduce a workflow to infer shale composition that combines seismic data, well logs, and laboratory measurements. It is applied to the Duyfken 3D seismic survey in the central part of the Northern Carnarvon Basin. Results of the interpretation are verified against laboratory XRD measurements from a test well that was not used for interpretation. The results match the test data well within the determined uncertainty bounds. Previously unpublished knowledge of shale mineralogical composition allows for a further analysis of the rock physics properties such as hydraulic permeability which is crucial for reservoir engineering and fluid flow simulations for CO2 sequestration and nuclear waste disposal.